The Reopening of Schools and Adoption of Universal Wearing of Face Masks in Anticipation of Sustained Transmission or the Second Wave of COVID-19 with the Influenza Virus - Lee, Cameron Y. S. (Journal of Public Health International, 2020)
The Covid-19 pandemic has swept rapidly from Wuhan, China to the entire globe in less than six months, infecting over 7 million people and claiming the lives of over 500,000. In the United States, greater than 2 million individuals have become infected and over 110,000 people killed. With no evidence of slowing of the coronavirus that causes Covid-19, public health authorities must prepare for possible sustained transmission of Covid-19, or a second wave into the Fall 2020, but with the presence of the influenza A virus. In the Fall 2020, schools will reopen from kindergarten to 12th grade. Dual pandemics or epidemics will result in high morbidity and mortality not observed when either virus was solely active. Community leaders, educational administrators and public health systems must be prepared for simultaneous outbreaks of both Covid-19 and influenza. Although there are no clinical studies that have evaluated the benefits on the use of face masks during an epidemic or pandemic, public health non-pharmaceutical intervention (NPIs) measures should include the routine use of face masks during school sessions. Using face masks with other NPI may interrupt viral transmission as it has been established that respiratory viruses, such as Covid-19 and the influenza virus are transmitted via respiratory droplets, aerosols, and environmental surface contact.
Keywords: Covid-19; Influenza; Universal; Face Masks; Pandemic; Schools